2014
DOI: 10.2341/12-235-l
|View full text |Cite
|
Sign up to set email alerts
|

Bonding of Y-TZP to Dentin: Effects of Y-TZP Surface Conditioning, Resin Cement Type, and Aging

Abstract: The application of the low-fusing glaze porcelain followed by hydrofluoric acid etching and silanization and tribochemical silicatization generates strong bonds between resin cement and zirconia. Panavia generates stronger bonds than does Clearfil. SUMMARYPurpose: To evaluate the effects of two surface treatments, aging, and two resin cements on shear bond strength between dentin and yttrium-stabilized tetragonal zirconia polycrystal ceramic (Y-TZP).Materials and Methods: Eighty human molars were embedded in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
1
7

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 26 publications
0
56
1
7
Order By: Relevance
“…The surface of the zirconia is coated with a thin layer of silica-based porcelain 33. Glazed surface can etch by HF and the silanization can be applied 34. A previous study reported higher bond strength values for indirect composite material-zirconia ceramics with the glaze layer & HF application 20…”
Section: Introductionmentioning
confidence: 99%
“…The surface of the zirconia is coated with a thin layer of silica-based porcelain 33. Glazed surface can etch by HF and the silanization can be applied 34. A previous study reported higher bond strength values for indirect composite material-zirconia ceramics with the glaze layer & HF application 20…”
Section: Introductionmentioning
confidence: 99%
“…For achieving long-term clinical success, various approaches have attempted the improvement of the bonding between zirconia and either veneering ceramics or cement materials [8,9,10,11,12,13]. Modification of the zirconia framework and sandblasting (airborne abrasion) of zirconia surfaces have been recommended to improve the fracture resistance of veneering ceramics [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, for bonding of zirconia to cement materials, an in vitro systematic review summarized seven surface treatment methods with 23 different procedures [10]. Generally, a tribochemical method such as sandblasting with alumina (Al 2 O 3 ) particles has been used to adapt the zirconia surface [11,12]. Furthermore, silanization by silane coupling agents or universal adhesive primers after silicatization has improved zirconia bonding to cement materials [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resin cement/zirconia ceramic interface was less susceptible to failures, owing to the zirconia ceramic surface treatments. 15 An analysis showed that bond strengths of the luting cement tested on the dental ceramics following surface conditioning methods varied according to ceramic type. Hydrofluoric acid gel was effective mostly on the ceramics that had a glassy matrix in their structures.…”
Section: Discussionmentioning
confidence: 99%